Women and educational leadership - Grogan, Margaret, 1952- (Jossey-Bass leadership library in education., 2011)
"In this book, the authors present a new way of looking at leadership that is grounded in research on women leaders. They flesh out what this kind of leadership looks like in practice and offer suggestions and ideas for how such leadership can be developed. Topics covered include women in educational leadership roles, women's way of leading, women in education overcoming obstacles, women in leadership roles for specific purposes, new tradition of leadership for women in education, the next generation of women leaders in education"--